Photocatalytic reduction of uranium(VI) by magnetic ZnFe2O4 under visible light - Liang, Peng-liang; Yuan, Li-yong; Deng, Hao; Wang, Xu-cong; Wang, Lin; Li, Zi-jie; Luo, Shi-zhong; Shi, Wei-qun (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Visible-light-driven photoreduction of U(VI) is achieved using ZnFe2O4 as catalyst.•50 ppm of uranium(VI) was almost completely removed in 60 min.•The photocatalytic activity of ZnFe2O4 is dependent on its morphology.•ZnFe2O4 rods own good stability, recyclability and magnetic separability. Visible-light-driven photocatalytic reduction of uranium(VI) is becoming an effective manner to remove uranium(VI) from waste water, whereas applicable catalysts are extremely limited. Herein, we report a first study of visible-light-driven photocatalytic reduction of uranium(VI) using visible light responsive ZnFe2O4. The ZnFe2O4 catalysts with different morphologies were successfully obtained and well characterized. The photoreduction of uranium(VI) under visible light was achieved over these ZnFe2O4 samples with the activity order of rods > microspheres > nanoparticles. Using ZnFe2O4 rods, for example, the 50 ppm of uranium(VI) was almost completely removed in 60 min, representing one of the most effective visible-light-driven photocatalytic removal. The effects of catalyst dosage, hole scavenger (CH3OH) dosage and solution pH on the photocatalytic reactions, as well as the photoreduction mechanisms were investigated in detail. In addition, ZnFe2O4 rods own good stability, recyclability and magnetic separability. All these features make ZnFe2O4 a promising photocatalyst for radioactive environmental remediation.